2022
DOI: 10.3389/fsurg.2022.938962
|View full text |Cite
|
Sign up to set email alerts
|

Laparo-endoscopic management of chole-choledocholithiasis: Rendezvous or intraoperative ERCP? A single tertiary care center experience

Abstract: IntroductionThe management of chole-choledocholithiasis remains a matter of debate to preserve minimal invasive management and different options have been proposed, with single- or two-stage approaches. Two techniques of single-stage approach are intraoperative ERCP and laparoscopic rendezvous, which have the great advantage of reducing the length of hospital stay with increased patient compliance. This retrospective study aims to evaluate and compare the efficacy and safety of intraoperative ERCP and rendezvo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…In current retrospective research from Italy done by Lagouvardou et al, the median stage II time was 15 minutes (range of 12-22 minutes) (8).…”
Section: Discussion Discussionmentioning
confidence: 86%
“…In current retrospective research from Italy done by Lagouvardou et al, the median stage II time was 15 minutes (range of 12-22 minutes) (8).…”
Section: Discussion Discussionmentioning
confidence: 86%
“…However, the intraoperative rendezvous group had a longer operative time but less postoperative pancreatitis, morbidity and hospitalization[ 30 ]. A recent retrospective study from Italy demonstrated that laparoscopic rendezvous shortened the endoscopic time and may be a reasonable alternative to intraoperative ERCP[ 31 ].…”
Section: Managementmentioning
confidence: 99%
“…After decades of development, ERCP has many advantages, such as less trauma, less pain, faster recovery, and fewer postoperative complications, and is widely used for diagnosing and treating choledocholithiasis[ 10 ]. The primary and emerging procedures of ERCP include endoscopic sphincterotomy (EST), endoscopic papillary balloon dilation (EPBD), endoscopic sphincterotomy plus balloon dilation (ESBD), and endoscopic endoclip papilloplasty (EEPP)[ 11 ].…”
Section: Introductionmentioning
confidence: 99%